Analisis Pembuatan Permainan Olahraga Terhadap Kreatifitas Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah - Putra, Andhika Yahya; Rahman, Alvin Yanuar; Putra, Roy Try (STAMINA, 2024)
The difference in priorities for sports education between religious universities and general universities with dedicated sports faculties is a natural occurrence. This is evidenced by the limited credit hours allocated to sports courses and the distinct characteristics of students at the outset, who tend to dislike sports, citing reasons such as fatigue and boredom. This study aims to examine the impact of sports game creation assignments on the creativity of students in the Madrasah Ibtidaiyah Teacher Education program. The research employs a qualitative descriptive approach. The subjects of the study are 100 students enrolled in the Madrasah Ibtidaiyah Teacher Education program at UIN Sunan Kalijaga for the academic year 2023–2024. Data collection techniques include surveys and interviews. The findings reveal that approximately 80% of students became more enthusiastic, confident, challenged, creative, and quicker at making risky decisions. However, not all students experienced the same outcomes, as other factors influencing the learning process may have hindered their creativity. These factors could be explored in future research.